Z problematyki emigracji z Grecji do Polski Ludowej - Chrisidu-Budnik, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The 1944–1949 Greek civil war between the supporters of the monarchy with the right-wing government and the left-wing forces with the Democratic Army of Greece resulted in the death of approximately 100,000 people and forced partisans and their families to migrate to countries of “people’s democracy.” It is estimated that the Polish People’s Republic accepted approximately 14,000 people (children and adults). The article describes the genesis of the conflict that led to the outbreak of the civil war as well as the increasing polarization of the Greek population. It presents the (political and social) complexity of the processes of emigrating from Greece to the people’s democracies and selected aspects of the organization of the Greek community’s life in the Polish People’s Republic.
Keywords: uchodźcy; emigracja; wojna domowa